Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan CV Gudang Fashion 26 - Arinda, Destiana; Akbar, Ridho Riadi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to describe job satisfaction, leadership style, and work discipline and analyze the influence of leadership style and work discipline on employees' job satisfaction at CV Gudang Fashion 26. The research employs a quantitative method with descriptive and verification approaches. The sample was taken using a saturated sampling technique involving 50 CV Gudang Fashion 26 employees, and data was collected through a questionnaire. Data analysis includes multiple linear regression, partial and simultaneous tests, and the coefficient of determination. Descriptive analysis shows a job satisfaction score of 893, a leadership style score of 876, and a work discipline score of 908, all in the high category. The results indicate that leadership style does not influence job satisfaction, while work discipline does. Simultaneously, leadership style and work discipline influence job satisfaction, with a contribution of 62.6%.